Income and health in different welfare contexts: A comparison of Sweden, East and West Germany. Issue 3 (May 2013) - Miething, Alexander; Lundberg, Olle; Geyer, Siegfried
Background : The aim of the present study is to explore whether the association between income and self-rated health in Sweden is similar to that in Germany. Both countries represent relatively similar economic contexts, but also different welfare traditions and historic experiences. Thus, the study compares Sweden with East Germany and West Germany in order to incorporate the aftereffects of reunification in East Germany. Methods : The association between adjusted disposable household income and self-rated health is investigated by exploring cross-sectional survey data for the year 2000. In a sequence of logistic regression models, the risk for poor self-rated health across income quintiles is analysed, controlling for educational status and occupational position. Data sources are the Swedish Level-of-Living Survey and the German Socio-Economic Panel. Results : A relationship between income and health was observed for Sweden, East Germany and West Germany, before as well as after controlling for education and occupational position. The associations were somewhat stronger for women than for men. Similar magnitudes of income-related poor health were detected across the investigated subsamples, but patterns were distinct in the three regions. The highest estimates were not always found in groups with the lowest income position. Conclusions : Given the variation in the results, we found neither advantages nor disadvantages that can be linked to the effectiveness of the welfare contexts under study. We could also not identify an income threshold for poor health across the investigated countries and settings. Nevertheless, the association between income and health persists, although the patterns vary across regional contexts .